PENGARUH TUNJANGAN, DIKLAT DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP DAN KEHUTANAN KABUPATEN KUTAI KARTANEGARA - Futum Hubaib (Prodi Ilmu Administrasi Negara, 2019)
Work productivity is something that is expected by every organization,both government and private organizations. Achieving optimal workproductivity means a success for the organization, which in turn will befeedback for the achievement of the objectives of employees and organizationsconcerned.To support work productivity at the maximum Environmental andForestry Service of Kutai Kartanegara Regency, there are at least 3 (three)important factors that must be considered, namely: first, adequate benefits sothat employee productivity is maintained while carrying out their duties;second, continuous education and training so that the ability and skills ofemployees always develop in accordance with the demands of work that alsocontinues to grow; and third, work discipline that functions as a controllinginternal control and regulations that regulate employees to work better andhave a passion for achievement in accordance with applicable workprocedures in the work agency.